A2_1 Extreme Football Curves - Dickens, Elliott; Anderson, Dominic; Limbu, Sandip; Bhaad, Trisha (Physics Special Topics, 2022)
In this paper, we investigate the conditions needed to kick a ball to form a complete loop. We compare our model to one of the most documented kicks in history, Roberto Carlos' famous free kick against France. We find that our model is in agreement with Carlos' kick, but from our analysis of the initial conditions, it is not possible to form a complete loop with our model.